Total and differential WBC counts are related with coronary artery atherosclerosis and increase the risk for cardiovascular disease in Koreans - Kim, Jung Hee; Lim, Soo; Park, Kyong Soo; Jang, Hak Chul; Choi, Sung Hee (PloS one, 2017)
Inflammation is a key mechanism of atherosclerosis. White blood cells (WBCs) play a pivotal role in the inflammatory process. We investigated the relationships between total and differential WBC counts and multi-detector cardiac computed tomography (MDCT) findings, as well as the risk of cardiovascular disease in asymptomatic patients in Korea. We recruited asymptomatic men (n = 7274) and women (n = 5478) aged ≥30 years who were free of known coronary heart disease. All patients underwent MDCT during a routine health check-up in the Seoul National University Bundang Hospital between 2006 and 2007, and were followed-up for 5.6 years. We reviewed medical records for cardiovascular diseases (CVDs) and covariates. In covariate-adjusted logistic regression models for MDCT findings, subjects within the third tertile of all WBC subtypes had a higher risk for significant stenosis and noncalcified plaques compared with the first tertile of each subtype. In Cox proportional hazard regression models for the risk of CVDs, subjects within the third tertiles of lymphocytes and monocytes were at an increased risk of CVDs (total WBC, HR = 1.22 [1.02-1.44]; lymphocyte, HR = 1.47 [1.25-1.74]; monocytes, HR = 1.26 [1.02-1.35]) even after further adjustment for covariates and coronary artery stenosis. Total WBC counts were related with the severity of coronary artery disease, and higher WBC counts increased the risk of CVDs in asymptomatic Koreans mainly by virtue of monocytes.